ABC of impossibility - Critchley, Simon, 1960- (Pharmakon (Minneapolis, Minn.), 2015)
An experimental text of para-philosophical fragments working toward a poetic ontology. How does one write an experimental ABC: an impossible theory that would deal with a series of phenomena, concepts, places, sensations, persons, and moods? A para-philosophy? Returning to a once abandoned project of fragmented thoughts where the author's voice moves from the serious, to the pathetic, to the absurd, to the cynical, Simon Critchley's ABC of Impossibility finds new life in the form of this small encyclopedic and aphoristic text where the reader bears witness to the slow emergence of an attempt at a poetic ontology. ABC of Impossibility is a unique undertaking that returns to the poetic site of the fragment as thought. Following a heritage of fragmented, aphoristic thinkers including Pascal, Nietzsche, Kierkegaard and Pessoa, Critchley revitalizes a para-philosophical thinking that can only be uttered by way of another, as he declares in the opening pages, "In writing this, I promise to tell the truth, but not to be myself."